The Analysis of Code Switching used by Cinta Laura in Kick Andy Show "Metro TV" Youtube Channel - Lolita Dwi Lorensa Deva Devita; Senowarsito; Dias Andris Susanto (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
This final project, titled "Analysis of Code Switch Used by Cinta Laura in Kick Andy Show on YouTube Channel 'Metro TV'", examines a Video posted on December 12, 2022. The research categorizes the types, functions, and contexts of code-switching used by Cinta Laura. Utilizing Hoffman's theory (1991) for type and context analysis, and Gumperz's theory (1982) for function analysis, this qualitative study reveals that in the 57 utterances analyzed, Intra- Sentential switching was the most frequent type (68.42%). Functions identified include message qualification and personalization versus Objectification (37.5%). Contexts included being emphatic and clarifying speech  content, Accounting for 35.09% of utterances. Data collection involved watching, analyzing, Recording, and classifying the video..